Study of synthesis parameters of MIL-53(Al) using experimental design methodology for CO/CH separation - Armin Taheri; Ensieh Ganji Babakhani; Jafar Towfighi (Adsorption Science & Technology)
In this study hydrothermal method was used to synthesize MIL-53(Al) (MIL stands for Materials Institute of Lavoisier). Plackett–Burman (P–B) as an experimental design method was applied to investigate the effect of synthesis and activation conditions on specific surface area, relative crystallinity, and production yield of MIL-53(Al) synthesis. Some parameters such as ligand-to-metal molar ratio, synthesis time, synthesis temperature, calcination temperature, and calcination time were selected as the variables. The Brunauer–Emmett–Teller (BET) technique was used in order to estimate the specific surface area of samples while the relative crystallinity of the samples was estimated by comparing their X-Ray Diffraction (XRD) pattern. The morphology of the samples was investigated by field emission scanning electron microscopy. The yield of final products was determined based on organic ligands. The results revealed the significant effect of synthesis temperature on BET surface area, particle size, yield, and crystallinity. The calcination temperature has significant positive effect on BET and crystallinity. Also, the negative significant effect of molar ratio on yield was concluded from the results. However, negligible effect of synthesis and calcination time on the properties of prepared materials were observed. Furthermore, separation capability of a selected sample for carbon dioxide (CO 2 ) and methane (CH 4 ) was measured. Pure gas adsorption data were successfully fitted to Langmuir, Sips, and Toth models. The selected sample provided high adsorption capacity for both gases. The binary adsorption of gases was also investigated based on extended Langmuir equations and the ideal adsorbed solution theory (IAST) models. Comparing the experimental and models data indicated good agreement between the IAST model and experiments. Finally, high CO 2 /CH 4 selectivity of 7.6 was obtained experimentally for the CO 2 /CH 4 molar ratio of 0.2/0.8.